Hehe z obliczeniami jak można ; ]]

Opuść nawiasy i zredukuj wyrazy podobne:
a) (3x+4y+2z)-(-2x+4y-5z)-(x+3y-2z)=
b) (x-2y-3z)-(3x+2y+z)+(4x-3y-3z)=
c) -(x²-3x+2)+(4-3x+2x²)-(7+4x-3x²)=
d) -(3-2x+4x²-2x³)+(-³-2x²-2x-6)=

Zredukuj wyrazy podobne :
a) -3a+6b-4+2a+2b-3=
b) 5a-4b+2-9a-2b-5=
c) x+3y-7z-3x+2y-z+2x-4y+2z=
d) -2x+4y-5z-2y-4z+3x+3z-2x+4y=
e) -2x²-5x+3-6x-2+x²+3x²+2x-8=

2

Odpowiedzi

2010-02-28T23:19:46+01:00
A) (3x+4y+2z)-(-2x+4y-5z)-(x+3y-2z)=
=3x+4y+2z+2x-4y+5z-x-3y+2z =
=4x-3y+9z

b) (x-2y-3z)-(3x+2y+z)+(4x-3y-3z)=
=x-2y-3z-3x-2y-z+4x-3y-3z=
=2x-7y-7z

c) -(x²-3x+2)+(4-3x+2x²)-(7+4x-3x²)=
= -x²+3x-2+4-3x+2x²-7-4x+3x²=
= 4x²-4x-5

d) -(3-2x+4x²-2x³)+(-x³-2x²-2x-6)=
= -3+2x-4x²+2x³- x³ -2x²-2x-6=
= x³-6x² -9


a) -3a+6b-4+2a+2b-3=
= a+8b-7

b) 5a-4b+2-9a-2b-5=
= -4a-6b-3

c) x+3y-7z-3x+2y-z+2x-4y+2z=
= y-6z

d) -2x+4y-5z-2y-4z+3x+3z-2x+4y=
= -x+6y-6z

e) -2x²-5x+3-6x-2+x²+3x²+2x-8=
= 2x² +9x -7
Najlepsza Odpowiedź!
2010-02-28T23:28:03+01:00
A)
(3x+4y+2z)-(-2x+4y-5z)-(x+3y-2z)=
=3x+4y+2z+2x-4y+5z-x-3y+2z=3x+2x-x+4y-4y-3y+2z+5z+2z=4x-3y+9z

b)
(x-2y-3z)-(3x+2y+z)+(4x-3y-3z)=
=x-2y-3z-3x-2y-z+4x-3y-3z=x-3x+4x-2y-2y-3y-3z-z-3z=2x-7y-7z

c)
-(x²-3x+2)+(4-3x+2x²)-(7+4x-3x²)=
-x²+3x-2+4-3x+2x²-7-4x+3x²=-x²+2x²+3x²+3x-3x-4x-2+4-7=4x²-4x-5

d)
-(3-2x+4x²-2x³)+(-x³-2x²-2x-6)=
=-3+2x-4x²+2x³-x³-2x²-2x-6=2x³-x³-4x²-2x²+2x-2x-3-6=x³-6x²-9


Zredukuj wyrazy podobne :

a) -3a+6b-4+2a+2b-3=-3a+2a+6b+2b-4-3=-a+8b-7

b) 5a-4b+2-9a-2b-5=5a-9a-4b-2b+2-5=-4a-6b-3

c) x+3y-7z-3x+2y-z+2x-4y+2z=x-3x+2x+3y+2y-4y-7z-z+2z=y-6z

d) -2x+4y-5z-2y-4z+3x+3z-2x+4y=-2x+3x-2x+4y-2y+4y-5z-4z+3z=
=-x+6y-6z

e) -2x²-5x+3-6x-2+x²+3x²+2x-8=-2x²+x²+3x²-5x-6x+2x+3-2-8=
=2x²-6x-7
1 5 1